Spent tea leaves as an adsorbent for micro solid phase extraction of polycyclic aromatic hydrocarbons in different matrices / Nazzatul Atirah Mohd Nazir - Nazzatul Atirah , Mohd Nazir (2021)
Food and water may be contaminated by hazardous pollutants, one of is a polycyclic aromatic hydrocarbon (PAHs), where 16 of pollutant in this group listed as a priority pollutant by Environmental Protection Agency (EPA). Thus, analysis of food contaminations is crucial for consumer safety. Therefore, a simple, sensitive, and miniaturize sample preparations are needed. In this study, spent tea leaves (STL), a waste from brewed tea, Camellia sinensis was utilized as novel micro-solid phase extraction (μ-SPE) sorbent for the determination of polycyclic aromatic hydrocarbon (PAHs) for the first time. It was of interest that spent tea leaves (STL) might serve as a suitable sorbent due to the presence of a variety of functional groups like lignin, cellulose, hemicellulose, and polyphenols that naturally can interact and adsorb the hydrophobic PAHs from real samples. STL was characterized by Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscope (FESEM), and energy dispersive x-ray analysis (EDX). Besides that, the interactions between PAHs and STL were proven by FT-IR, FESEM, and EDX analysis. Moreover, a key parameter in the extraction efficiency of STL based μ- SPE, such as eluent type and volume, the dosage of sorbent, extraction and desorption time, and volume of the sample was examined. Finally, an effective, environmentally friendly, and economic STL based tea bag filter as porous membrane protected STL-μ-SPE method for the determination of five types of PAHs (Flu, Flt, Pyr, Chr, and BaP) was developed and successfully applied in the analysis of water, rice, orange, and apple juice samples. Under the optimized conditions, the matrix matched calibration curves were linear in the range of 50 ng mL-1 to 1000 ng mL-1 and the coefficient of determinations (R2) found to be between 0.9947 and 0.9983. The LOD and LOQ of liquid and solid sample is in range of 8.47-55.95 ng mL-1, 2.98-30.22 μg kg-1 and 28.23-186.54 ng mL-1, 9.04- 91.59 μg kg-1. While the intra-day and inter-day precision (n=6) were found to be between 5.23 % to 7.76 % and 6.90 % to 10.86 %, respectively. The recovery values in the real samples are between 88.0 % and 111.4 % and its RSDs (n=3) from 1.0 % to 9.8 %. The present method found to be fast, sensitive, cost-effective, reproducible, and this work also introduces a new application method of the agricultural crop in the determination and quantification of PAHs in real samples analysis.